Le ne explétif dans la traduction automatique - Hrabia, Michał (Neophilologica, 2016)
The aim of the present paper is to analyse the French ‘ne explétif’ for the purpose of its machine translation into Polish. The method of the study is based on object-oriented approach by Wiesław Banyś. In the first part, the author attempts to give a brief overview of the theories on the expletive negation. The second part is the analysis of the different uses of the ‘ne explétif’ and their Polish translations. The author distinguishes two types of the French ‘ne explétif’ in Polish : ‘nie without the value of negation’ and ‘pure expletive nie’. The results of the research are presented in ten syntacticsemantic schemes, i.e. in one of the computationally implementable formats of description used in the object-oriented approach.